Simultaneous spectrophotometric determination of food colorants employing multivariate calibration methods - Karuna Jainontee (2018)
This study investigated the simultaneous spectrophotometric determination of three food colorants - Tartrazine (T), Ponceau 4R (P) and Indigo carmine (I) - in mixtures employing multivariate calibration methods. Absorption spectra of 76 mixtures of the colorants were recorded. The 76 spectra were divided into three sets: calibration, validation and unknown. This study employed three multivariate calibration methods: principal component regression (PCR), partial least square 1 (PLS1) and partial least square 2 (PLS2). The study involved training set characteristics and signal characteristics. Concentration ranges and concentration ratios of the colorants were used as criteria in selection of training sets and found to be important parameters for predictive accuracy.